The Effects of Prophylactic Dexmedetomidine Administration on General Anesthesia Recovery Quality in Healthy Dogs Anesthetized With Sevoflurane and a Fentanyl Constant Rate Infusion Undergoing Elective Orthopedic Procedures - Jarosinski, Sarah K.; Simon, Bradley T.; Baetge, Courtney L.; Parry, Stephen; Araos, Joaquin (Frontiers in Veterinary Science, 2021)
To determine the effects of a dexmedetomidine slow bolus, administered prior to extubation, on recovery from sevoflurane-anesthesia and a fentanyl continuous rate infusion (CRI) in dogs undergoing orthopedic surgical procedures. Sixty-two client-owned, healthy dogs weighing 27.4±11 kg undergoing elective orthopedic procedures were premedicated with: 0.1 mg/kg hydromorphone intramuscular, 0.05 mg/kg hydromorphone intravenously (IV) or 5 mcg/kg fentanyl IV. Following premedication, dogs were induced with propofol, administered locoregional anesthesia and maintained with sevoflurane and a fentanyl CRI (5-10 mcg/kg/hr). Dogs were randomly assigned to one of two treatment groups: 0.5 mcg/kg dexmedetomidine (DEX) or 0.5 ml/kg saline (SAL). Following surgery, patients were discontinued from the fentanyl CRI and administered DEX or SAL IV over 10 minutes. Following treatment, dogs were discontinued from sevoflurane and allowed to recover without interference. Recoveries were video recorded for 5 minutes following extubation and assessed by two blinded anesthesiologists using a visual analog scale (VAS; 0-10 cm) and a numerical rating scale (NRS; 1-10). Mean arterial pressure (MAP), heart rate (HR), pulse oximetry (SpO2), temperature, respiratory rate (RR), and end-tidal sevoflurane (EtSevo) and carbon dioxide (EtCO2) concentrations were recorded at specific time-points from induction to five minutes post-bolus administration and analyzed using linear mixed models. Fentanyl, propofol, and hydromorphone dose and the time to extubation were compared using an unpaired t-test. Differences in recovery scores between groups were evaluated with a Mann-Whitney test. Data reported as mean±SD or median [interquartile range] when appropriate. A p value of < 0.05 was significant. There were no significant differences between groups in fentanyl, propofol, and hydromorphone dose, duration of anesthesia, intraoperative MAP, HR, RR, SpO2, temperature, EtCO2, EtSevo or anesthetic protocol. MAP was higher in DEX compared to SAL at 10 (104±27 and 83±23, respectively) and 15 (108±28 and 86±22, respectively) minutes after treatment. DEX had significantly lower VAS (0.88 [1.13]) and NRS (2.0 [1.5]) scores when compared to SAL (VAS=1.56 [2.59]; NRS=2.5 [3.5]). Time to extubation (minutes) was longer for DEX (19.7±11) when compared to SAL (13.4±10). Prophylactic dexmedetomidine improves recovery quality during the extubation period, but prolongs its duration, in sevoflurane-anesthetized healthy dogs administered fentanyl.